Development of an Approach of High Sensitive Chemiluminescent Assay for Cystatin C Using a Nanoparticle Carrier - Sun, Yuanjie; Tao, Liang; Ma, Ying; Yang, Shuya; Zhang, Xiyang; Jin, Boquan; Zhang, Zhujun; Yang, Kun (Frontiers in Chemistry, 2020)
Cystatin C is an important cysteine protease inhibitor in the human body and is proposed as a new indicator of glomerular filtration rate for the detection of kidney damage. In this article, we report an ultra-sensitive, simple, and rapid chemiluminescence immunoassay method for cystatin C detection using functionalized mesoporous silica nanoparticles. After a three step hydrolysis, the amino-functionalized MSN encapsulating dye resulted in a hydrophobic environment for fixing the dye and amino groups for biological modification. The NaIO4 immobilization method maintained the activity of the antibody notably well. The sandwich immunoassay using two monoclonal antibodies was chosen for its selectivity. The analysis demonstrated that the detection upper was 0.0029 ng/mL and linear relationship within the range of 0.0035–0.5 ng/mL (R2 = 0.9936). The relative standard deviation (RSD) for 11 parallel measurements of 0.25 ng/mL CysC was 4.7%. The automated chemiluminescence analyzer could detect 96 wells continuously. The results demonstrated that this method is ultra-sensitive, simple, and rapid for detecting cystatin C.